PENGARUH PENERAPAN BAHAN AJAR TERINTEGRASI NILAI-NILAI KARAKTER DALAM MODEL PEMBELAJARAN KOOPERATIF TIPE CORE PADA MATERI USAHA ENERGI DAN GETARAN HARMONIS SEDERHANA TERHADAP KOMPETENSI SISWA KELAS XI SMA N 1 TARUSAN - Pratiwi Mailisa; Masril Masril; Yenni Darvina (Universitas Negeri Padang, 2017)
This study aims to investigate the effect of implementation of integrated learning material character values in CORE Cooperative learning Model in business Matter Energy and Simple Harmonic Vibrations Competence against student class XI SMAN 1 Tarusan. The research is a Quasi Experiment with Randomized Control Research Group Only Design with a population of this research is a class XI student of SMAN 1 Tarusan listed in the Academic Year 2016/2017. Sampling was done by purposive sampling technique. Data collection tool of research in the form of a written test for competency knowledge and competency observation sheet for the scoring rubric for the attitude and competence skills. Mechanical analysis of research data using the t test at real level of 0.05 for the third competency. Based on the analysis of data obtained by the average value for the experimental class and control class that is in the competence of knowledge (80.97) and (72.26), the competence of the attitude that (86.11) and (81.39), and competence skills that (85.3) and (83.59). Data knowledge of both classes of normally distributed samples and having variances were homogeneous, so do test the equality of two average. Competence knowledge tcount (3,537), competence, attitudes tcount (7.25), and competence skills tcount (1.025) with table = 2.00. Thus the working hypothesis that reads Effect of Application of Instructional Materials Integrated Values Characters in Cooperative Learning Model Core At Creative Enterprises Energy and Vibration Harmonic Simple Against Student Competency Class XI SMAN 1 Tarusan accepted for aspects of competence knowledge and attitudes but not for competency skills